Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.celrep.2016.09.055
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Dendritic Cells Confer Protection against Mouse Cytomegalovirus Infection via TLR9 and MyD88 Signaling

Abstract: Cytomegalovirus (CMV) is an opportunistic virus severely infecting immunocompromised individuals. In mice, endosomal Toll-like receptor 9 (TLR9) and downstream myeloid differentiation factor 88 (MyD88) are central to activating innate immune responses against mouse CMV (MCMV). In this respect, the cell-specific contribution of these pathways in initiating anti-MCMV immunity remains unclear. Using transgenic mice, we demonstrate that TLR9/MyD88 signaling selectively in CD11c dendritic cells (DCs) strongly enhan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 61 publications
6
28
0
Order By: Relevance
“…Murine cDC on the other hand can be infected with MCMV but produce smaller amounts of type I IFNs (20,28). In vivo experiments have shown that DC contribute to the control of CMV infection by indirect mechanisms inducing antiviral responses of NK and T cells (27,(29)(30)(31). More recently, we showed direct repression of MCMV infection and spread by bone marrow-derived DC (mDC) (22) in coculture with infected endothelial and fibroblast cells.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Murine cDC on the other hand can be infected with MCMV but produce smaller amounts of type I IFNs (20,28). In vivo experiments have shown that DC contribute to the control of CMV infection by indirect mechanisms inducing antiviral responses of NK and T cells (27,(29)(30)(31). More recently, we showed direct repression of MCMV infection and spread by bone marrow-derived DC (mDC) (22) in coculture with infected endothelial and fibroblast cells.…”
mentioning
confidence: 94%
“…Nevertheless, there are significant similarities between CMVs of different species at the level of viral genes and their functions (23)(24)(25), and the murine CMV (MCMV) is widely used as model of virus-host in vivo interactions. Murine pDC are the major source of a type I interferon response to MCMV infection (26) yet do not support a replicative infection (27). Murine cDC on the other hand can be infected with MCMV but produce smaller amounts of type I IFNs (20,28).…”
mentioning
confidence: 99%
“…The mechanisms accounting for the activation of cDC also remain to be determined. cDCs could be either directly activated via TLR9 ligation (53) or indirectly activated with other cell types mediating the signaling between CpG-B and cDC activation. In contrast to previous observations (20), we excluded a possible role for IFN-I in the activation of cDC after i.t.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, murine TLR9 is expressed abundantly in myeloid immune cells and can also result in IFN-γ production and the recruitment of NK, αβ-, and γδ-T cells (Hartmann, 2017; Hornung et al, 2002; Krug et al, 2004; Walker et al, 2010). For example, it has been shown that CMV infection in mice activates a TLR9/MyD88 response that occurs selectively in CD11 + dendritic cells (Krug et al, 2004; Puttur et al, 2016). Other DNA viruses that have been implicated in activating an innate immune response through TLR9 are Varicella zoster virus (VZV), Epstein-Barr virus (EBV), Kaposi sarcoma-associated herpesvirus (KSHV), vaccinia virus (VV), adenovirus (AdV), and human CMV (Appledorn et al, 2008; Basner-Tschakarjan et al, 2006; Fiola et al, 2010; Lim et al, 2006; Samuelsson et al, 2008; Varani et al, 2007; West et al, 2011; Yu et al, 2011).…”
Section: Intracellular Recognition Of Dnamentioning
confidence: 99%